Building Transnational Bodies: Norway and the International Development of Laboratory Animal Science, ca. 1956–1980. Issue 2 (29th April 2014) - Druglitrø, Tone; Kirk, Robert G. W.; Gradmann, Christoph; Asdal, Kristin
Argument This article adopts a historical perspective to examine the development of Laboratory Animal Science and Medicine, an auxiliary field which formed to facilitate the work of the biomedical sciences by systematically improving laboratory animal production, provision, and maintenance in the post Second World War period. We investigate how Laboratory Animal Science and Medicine co-developed at the local level (responding to national needs and concerns) yet was simultaneously transnational in orientation (responding to the scientific need that knowledge, practices, objects and animals circulate freely). Adapting the work of Tsing (2004), we argue that national differences provided the creative "friction" that helped drive the formation of Laboratory Animal Science and Medicine as a transnational endeavor. Our analysis engages with the themes of this special issue by focusing on the development of Laboratory Animal Science and Medicine in Norway, which both informed wider transnational developments and was formed by them. We show that Laboratory Animal Science and Medicine can only be properly understood from a spatial perspective; whilst it developed and was structured through national "centers, " its orientation was transnational necessitating international networks through which knowledge, practice, technologies, and animals circulated.